Politik Hukum Pembentukan Undang-Undang Aparatur Sipil Negara: Implikasinya terhadap Dosen di Perguruan Tinggi Negeri - Intan Permata Sari; Irsyaf Marsal (AHKAM, 2025)
Indonesia, as a rechtstaat (rule of law) state, implicitly adopts the principles of a welfare state, one of which is reflected in the regulation of the national civil service system. Following the enactment of Law Number 20 of 2023 concerning State Civil Apparatus (UU ASN 2023), the management of civil servants has become more organized and adaptive to the needs of government institutions. However, this regulation presents normative issues, particularly for non-civil servant (non-PNS) lecturers at public universities. This study aims to examine the legal politics behind the enactment of UU ASN 2023 and its implications for the regulation of lecturers within the public higher education system. A normative juridical method was employed, utilizing statutory and conceptual approaches. The findings indicate that the legal politics of UU ASN 2023 are directed at reforming civil servant management to be more flexible and competitive, including in the recruitment of talent in the public sector. Nonetheless, the implementation of this regulation generates normative conflicts with Law Number 14 of 2005 on Teachers and Lecturers (UU Guru Dosen), particularly regarding the recognition of non-PNS lecturers in public universities. Therefore, in drafting implementing regulations for UU ASN 2023, the government should refer to UU Guru Dosen as lex specialis to ensure legal certainty and continuity for non-PNS lecturers. These findings underscore the importance of regulatory harmonization in the higher education sector to prevent legal uncertainty and to safeguard the professional rights of lecturers.